LDL particle size and composition and incident cardiovascular disease in a South-European population: The Hortega-Liposcale Follow-up Study. (1st August 2018) - Pichler, G.; Amigo, N.; Tellez-Plaza, M.; Pardo-Cea, M.A.; Dominguez-Lucas, A.; Marrachelli, V.G.; Monleon, D.; Martin-Escudero, J.C.; Ascaso, J.F.; Chaves, F.J.; Carmena, R.; Redon, J.
Abstract: Background: The association of low-density lipoprotein (LDL) particle composition with cardiovascular risk has not been explored before. The aim was to evaluate the relationship between baseline LDL particle size and composition (proportions of large, medium and small LDL particles over their sum expressed as small-LDL %, medium-LDL % and large-LDL %) and incident cardiovascular disease in a population-based study. Methods: Direct measurement of LDL particles was performed using a two-dimensional NMR-technique (Liposcale®). LDL cholesterol was assessed using both standard photometrical methods and the Liposcale® technique in a representative sample of 1162 adult men and women from Spain. Results: The geometric mean of total LDL particle concentration in the study sample was 827.2 mg/dL (95% CI 814.7, 839.8). During a mean follow-up of 12.4 ± 3.3 years, a total of 159 events occurred. Medium LDL particles were positively associated with all cardiovascular disease, coronary heart disease (CHD) and stroke after adjustment for traditional risk factors and treatment. Regarding LDL particle composition, the multivariable adjusted hazard ratios for CHD for a 5% increase in medium and small LDL % by a corresponding decrease of large LDL % were 1.93 (1.55, 2.39) and 1.41 (1.14, 1.74), respectively. Conclusions: Medium LDL particles were associated with incident cardiovascular disease. LDL particles showed the strongest association with cardiovascular events when the particle composition, rather than the total concentration, was investigated. A change in baseline composition of LDL particles from large to medium and small LDL particles was associated with an increased cardiovascular risk, especially for CHD. Highlights: Medium LDL particle concentrations were associated with CVD, CHD and stroke incidence in a general population from Spain A change in baseline composition of LDL particles from large to medium and small LDL particles was associated with and increased cardiovascular risk Subjects with predominant small or medium LDL particles were characterized by an unfavourable cardiometabolic risk profile